DESIGNING OF SIMULATION FOR ENGINE ROOM KM. SINABUNG WITH CONTROL MONITORING WEB SERVER BASED BY WIRELESS NETWORK AND POWER LINE COMMUNICATION - Hadi, Eko Sasmito; Adietya, Berlian Arswendo; S.P, Firdaus (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2013)
Engine room monitoring control system is monitoring and controlling main engine and auxiliary engine from long distance by powerline communication network and wireless network to ease the operator in operating the ship and save operational cost. To prevent error in programming the main engine and auxiliary engine, a simulation using instrument software is needed to know the machine characteristic. After simulation result fulfills the requirement which is approached the value of test record, it can be applied to the real machine. In this study, some steps were done such as: getting know type of main engine and auxiliary engine which performance will be simulated and programmed, getting test record of main engine and auxiliary engine, getting know how the main engine and auxiliary engine work, making simulation of main engine and auxiliary engine work system, doing monitoring control simulation by powerline communication and wireless network, comparing the results between simulation and test record of main engine and auxiliary engine. Engine programming can be set after simulation result meets the requirement. Result of simulation fulfills the requirement, the difference values between machine simulation using software instrument and test record of main engine and auxiliary engine are around 1%-2%. If engine room monitoring control system by wireless and powerline communication is applied in the ship, the ship owner will get advantages because it will prolong ship durability and can monitor operasional of main engine or Auxiliary engine from long distance ; while the operator will be easier in operating the ship. The disadvantage is only the higher cost